A Rare Variant of the Stafne Bone Cavity Localized to the Subcondylar Region of the Mandible: A Case Report with Review of the Literature - Y. S. Lee, Cameron; L. Lee, Kristin (Journal of Clinical and Diagnostic Pathology, 2019)
An anatomical variant of the Stafne bone cavity (SBC) located in the right subcondylar region of the mandible is presented. Such an occurrence of the SBC in this region near the parotid gland is considered rare and poses a diagnostic challenge for the dentist and radiologist. Knowledge of head and neck clinical anatomy and imaging studies such as plain film panoramic radiographs and cone beam CT scans can assist the clinician in arriving at a correct definitive diagnosis without surgical intervention.
Keywords: Clinical anatomy; Stafne bone cavity (SBC); Anatomic variant; Subcondylar region; Parotid gland; Cone beam CT scan